Assessment of the impact of exercise therapy combined with family intervention on attention and executive function in children with attention deficit and hyperactive disorder - Jia Wang; Juan Zhang; Yi Shi; Fei Liu; Lihong Xiao; Xianglan Wen; Yinhong Chen (BMJ Paediatrics Open)
Objectives To evaluate the impact of exercise therapy combined with family intervention on attention and executive function in children diagnosed with attention deficit and hyperactivity disorder (ADHD).Methods This retrospective cohort study involved children diagnosed with ADHD and split them into two groups: the conventional treatment group (n=68) and the behavioural therapy combined with family intervention group (n=72). The intervention group received behavioural therapy combined with family intervention in addition to medication, while the conventional treatment group received medication and health education. Various assessment indicators were used to evaluate attention and executive function, physical activity levels, emotional regulation, social functioning, school performance, parental stress levels, parent-child relationship quality and parental knowledge about ADHD. Statistical analysis was conducted to compare the outcomes between the two groups.Results Postintervention attention function scores, executive function scores, social functioning and school performance scores were significantly higher in the behavioural therapy combined with family intervention group compared with the conventional treatment group. Postintervention parental stress levels were significantly lower in the intervention group, and parent-child relationship quality and parental knowledge about ADHD were significantly higher compared with the conventional treatment group. Correlation analysis demonstrated a positive relationship between the intervention and postintervention attention and executive functioning, social functioning, school performance and parental outcomes.Conclusion The findings suggest that exercise therapy combined with family intervention has the potential to improve attention and executive function, social functioning, school performance, parental well-being, and family dynamics in children with ADHD.